Preliminary investigation of the effect of ferulic acid on miRNAs and LncRNAs in Mongolian horse skeletal muscle satellite cells - Gong, Wendian; Ding, Wenqi; Bou, Tugeqin; Shi, Lin; Lin, Yanan; Shi, Xiaoyuan; Li, Zheng; Wu, Huize; Dugarjaviin, Manglai; Bai, Dongyi (Frontiers in Genetics, 2025)
IntroductionFerulic acid (FA), a natural antioxidant, has attracted considerable attention for its regulatory potential in skeletal muscle development, energy metabolism, and muscle fiber type transformation.MethodsThis study established a research system based on Mongolian horse skeletal muscle satellite cells to elucidate the molecular basis by which ferulic acid regulates muscle fiber type transformation through a non-coding RNA interaction network.ResultsA total of 18 differentially expressed miRNAs (DEMIRs) and 128 differentially expressed lncRNAs (DELs) were identified through transcriptome sequencing of the ferulic acid-treated (FA) group and the control group (NC). The target genes of non-coding RNAs are enriched in processes such as positive regulation of TOR signaling, cell migration, and positive regulation of vascular endothelial cell proliferation, where they play important roles in cell growth and proliferation. Dual luciferase reporter assays confirmed that LncRNA MSTRG.7632.14 competitively binds to eca-miR-6529, thereby relieving its inhibitory effect on PDK1 and forming a biologically functional regulatory axis.ConclusionThis study reveals that ferulic acid can regulate muscle fiber proliferation and type transformation through the interaction network of non-coding RNAs and target genes, providing potential targets for optimizing the athletic performance and muscle function of equids.